Klasifikasi Kelayakan Penerima PPKS Usulan BPNT dan PHK Lanjut Usia Non Tunai menggunakan Algoritma Cart di Kabupaten Seruyan - Nurahman, Nurahman; Sari, Aida Puspita; Deswanti, Karina Indah (CV. Information Technology Training Center - Indonesia (ITTC), 2023)
The purpose of this research is to classify the eligibility of recipients of Non-Cash Food Assistance (BPNT) and recipients of the Prosperous Family Program (PPKS) and (PHK) for the elderly proposed in Seruyan District using the CART (Classification and Regression Tree). Algorithm The purpose of the Living Allowance is to assist those in need in meeting their food and welfare needs, especially for underprivileged and elderly families. The research data was obtained through a direct survey of potential beneficiaries in Seruyan District. The data is then processed in the preprocessing stage to ensure good data quality before being used to develop the CART model. The CART model development stage is carried out by dividing the data into two parts, namely. training data and test data, to train and test model performance. The estimation results of the CART model show an accuracy of 87.50%, Precision of 87.50%, and Sensitivity or Recal of 100.00%. Analyzing the results revealed that socioeconomic factors such as family income, employment status, and housing conditions had a significant impact on beneficiary eligibility. These findings provide valuable information for improving social assistance distribution policies in Seruyan District so that assistance is more targeted and maximizes benefits for beneficiary communities. This study is expected to increase the effectiveness and efficiency of the distribution of income assistance and improve the quality of life of beneficiary communities. However, this research has limitations because it was only conducted in one district, so further research is needed with a more representative sample to ensure validity and wider application.